The fiction of the affecting object in Hans Vaihinger’s philosophy - Pringe, Hernan Bruno (2011)
This paper investigates the relationship between Vaihinger’s interpretation of the affecting object as a fiction and his analysis of the problem of affection in Kantian philosophy. We argue that the fictionalism of the affecting object seeks to solve the difficulties that Vaihinger finds in the Kantian doctrine of affection. Moreover, we show that Vaihinger’s position does not entail a complete renunciation of transcendental idealism, because a fictional transcendent affection can be fully justified within the framework of critical philosophy.